"Comet‐tailing" associated with gunshot entrance wounds. Issue 3 (7th April 2021) - Prahlow, Samuel P.; Brown, Theodore T.; Dye, Daniel; Poulos, Christopher; Prahlow, Joseph A.
Abstract: A "plated bullet" has a thin layer of electroplated metal covering the lead core of the projectile. In certain situations, this thin layer of electroplated metal can fracture upon discharge of the firearm. When such fracturing occurs, vaporous lead can escape through the fracture lines of the spinning projectile, resulting in a spiral‐shaped deposition of dark residue surrounding a central bullet defect. The spiral‐shaped pattern is referred to as "comet‐tailing, " or the "vortex effect." In this report, three homicide cases with associated comet‐tailing are presented. Police, death investigators, and forensic pathologists should be aware of this unique finding.